Perencanaan Manajemen Proyek Pembangunan Usaha Rumah Kost Millenial di Pamulang - Agung Wijoyo; Satria Putra Laksmana; Diva Ikbar Rauf; MUHAMAD BURHANUDIN; Damar Wicaksono (CV. Multi Kreasi Media, 2022)
The increase in the need for housing in the city of Pamulang is in line with the progress of all fields in Indonesia, be it in terms of economy, education, tourism, culture, and telecommunications. So that a boarding house rental business opportunity emerged. To be able to realize the boarding house business in the pamulang area, good project management planning and governance is needed, which is used regularly to complete small or large and complex projects. Project management is the main key to success in implementing and completing a project to be worked on. The main focus of project management is the application of all project goals with all existing constraints, time, price and available budget. The POAC management model (planning, organizing, actuating, controlling) is a management model that is commonly used, especially in management that requires more supervision. By using this management model, it can be seen that this business house construction project takes 1 year of work with an investment fund requirement of IDR 574,784.00. Return on Investment 9.8% per year.